Recent Advances in Producing Sugar Alcohols and Functional Sugars by Engineering Yarrowia lipolytica - Abbasi, Abdul Rahman; Liu, Jinle; Wang, Zhi; Zhao, Anqi; Ying, Hanjie; Qu, Lingbo; Alam, Md. Asraful; Xiong, Wenlong; Xu, Jingliang; Lv, Yongkun (Frontiers in Bioengineering and Biotechnology, 2021)
The sugar alcohols and functional sugars have wide applications in food, pharmaceutical, and chemical industries. However, the smaller quantities of natural occurring sugar alcohols and functional sugars restricted their applications. The enzymatic and whole-cell catalyst production is emerging as the predominant alternatives. The properties of Yarrowia lipolytica make it a promising sugar alcohol and functional sugar producer. However, there are still some issues to be resolved. As there exist reviews about the chemical structures, physicochemical properties, biological functions, applications, and biosynthesis of sugar alcohols and/or functional sugars in Y. lipolytica, this mini review will not only update the recent advances in enzymatic and microbial production of sugar alcohols (erythritol, D-threitol, and xylitol) and functional sugars (isomaltulose, trehalose, fructo-oligosaccharides, and galacto-oligosaccharides) by using recombinant Y. lipolytica but also focus on the studies of gene discovery, pathway engineering, expanding substrate scope, bioprocess engineering, and novel breeding methods to resolve the aforementioned issues.